Alternative NF-kappa B Signaling Discriminates Induction of the Tumor Marker Fascin by the Viral Oncoproteins Tax-1 and Tax-2 of Human T-Cell Leukemia Viruses - Heym, Stefanie; Mohr, Caroline; Engelbrecht, Hanna C.; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (Cancers, 2022)
Simple Summary:& nbsp;The actin-bundling protein Fascin is upregulated in many types of cancers, including adult T-cell leukemia/lymphoma, a tumor induced by the oncogenic retrovirus human T-cell leukemia virus type 1 (HTLV-1). Transcriptional regulation of Fascin is heterogeneous between different cell types and tissues, and Fascin is usually expressed at low levels in T-cells. We have previously shown that a single viral oncoprotein, Tax-1 of HTLV-1, is a potent inducer of Fascin in T-cells depending on classical NF-kappa B signaling. In this study, we discovered that transcriptional activation of Fascin by viral oncoproteins depends on activity of both the classical and the alternative NF-kappa B signaling cascade. Comparisons between Tax-1 and Tax-2 from the closely related but non-oncogenic HTLV-2 revealed that alternative NF-kappa B signaling discriminates transcriptional induction of Fascin by the Tax proteins encoded by HTLVs. Together, Tax-1 and Tax-2 proteins are useful tools to study oncogenic signaling in T-cells.& nbsp;Transcriptional regulation of the actin-bundling protein and tumor marker Fascin is highly diverse depending on cell and tumor type. Previously, we discovered that the viral oncoprotein Tax-1 of human T-cell leukemia virus type 1 (HTLV-1) considerably enhances Fascin expression in T-cells, depending on classical NF-kappa B signaling. In this study, we asked if the non-oncogenic Tax-2 of the related HTLV-2 is still able to induce Fascin by using luciferase assays, immunoblot, and qPCR. We found that Tax-2 only slightly induces Fascin expression compared to Tax-1; however, both Tax-1 and Tax-2 comparably activated a 1.6 kb fragment in the human Fascin promoter including Tax-responsive elements. Furthermore, we identified a link between Tax-induced activity of the alternative NF-kappa B pathway and Fascin induction. While treatment with the second mitochondria-derived activator of caspases (SMAC)-mimetic AZD5582, a compound known to robustly activate alternative NF-kappa B signaling, did not induce Fascin, combination of AZD5582 with activation of classical NF-kappa B signaling by Tax-2 significantly induced Fascin expression. In conclusion, our data demonstrate that both classical and alternative NF-kappa B activity are necessary for strong Fascin induction by the viral Tax oncoproteins, thus, shedding new light on the regulation of Fascin in T-cells and during viral transformation.
CRIS-Team WoS Importer:2022-03-11
Keywords: Fascin; tumor virus; HTLV-1; human T-cell leukemia virus type 1; alternative NF-κB; viral oncoprotein; Tax-1; Tax-2

A Novel Tax-Responsive Reporter T-Cell Line to Analyze Infection of HTLV-1 - Heym, Stefanie; Krebs, Pauline; Ott, Kristin; Donhauser, Norbert; Kemeter, Laura; Simon, Florian; Millen, Sebastian; Thoma-Kreß, Andrea (Pathogens, 2024)
Human T-cell leukemia virus type 1 (HTLV-1) infects CD4+ T-cells through close cell–cell contacts. The viral Tax-1 (Tax) protein regulates transcription by transactivating the HTLV-1 U3R promoter in the 5′ long terminal repeat of the integrated provirus. Here, we generated a clonal Tax-responsive T-cell line to track HTLV-1 infection at the single-cell level using flow cytometry, bypassing intracellular viral protein staining. Jurkat T-cells stably transduced with the SMPU vector carrying green fluorescent protein (GFP) under control of 18 × 21 bp Tax-responsive element repeats of the U3R were evaluated. Among 40 clones analyzed for Tax responsiveness, the top two were characterized. Upon overexpression of Tax, over 40% of the cells showed GFP positivity, and approximately 90% of the Tax-positive cells were GFP-positive, indicating efficient reporter activity. However, with CREB-deficient Tax mutant M47, both total GFP-positive cell counts and those within the Tax-positive group significantly decreased. Co-culture with chronically HTLV-1-infected MT-2 or C91-PL cells led to an average of 0.9% or 2.4% GFP-positive cells, respectively, confirming the suitability to monitor HTLV-1 transmission and that HTLV-1 infection is very low. Thus, the novel Tax-responsive reporter T-cell line is a suitable tool to monitor infection of HTLV-1 on the single-cell level.
CRIS-Team Scopus Importer:2024-12-06
Keywords: HTLV-1; HTLV-1 cell-to-cell transmission; HTLV-1 promoter; infection; reporter T-cell line; SMPU; Tax; Tax-responsive element; U3R

Milk Transmission of Mammalian Retroviruses - Kemeter, Laura; Birzer, Alexandra; Heym, Stefanie; Thoma-Kreß, Andrea (Microorganisms, 2023)
The transmission of viruses from one host to another typically occurs through horizontal or vertical pathways. The horizontal pathways include transmission amongst individuals, usually through bodily fluids or excretions, while vertical transmission transpires from mother to their offspring, either during pregnancy, childbirth, or breastfeeding. While there are more than 200 human pathogenic viruses to date, only a small number of them are known to be transmitted via breast milk, including cytomegalovirus (CMV), human immunodeficiency virus type 1 (HIV-1), and human T cell lymphotropic virus type 1 (HTLV-1), the latter two belonging to the family Retroviridae. Breast milk transmission is a common characteristic among mammalian retroviruses, but there is a lack of reports summarizing our knowledge regarding this route of transmission of mammalian retroviruses. Here, we provide an overview of the transmission of mammalian exogenous retroviruses with a focus on Orthoretrovirinae, and we highlight whether they have been described or suspected to be transmitted through breast milk, covering various species. We also elaborate on the production and composition of breast milk and discuss potential entry sites of exogenous mammalian retroviruses during oral transmission.
CRIS-Team Scopus Importer:2023-08-11
Keywords: breast milk; breastfeeding; human immunodeficiency virus (HIV); human T cell lymphotropic virus type 1 (HTLV-1); mammalian retrovirus; oral route; retrovirus; salivary glands; tonsils; virus transmission